Seismic Wave Propagation and Scattering in the Heterogeneous Earth - Sato, Haruo. (Modern Acoustics and Signal Processing, 2009)
Focusing on recent developments in the area of seismic wave propagation and scattering, this text combines information from numerous sources to present a coherent introduction to the theory of scattering in acoustic and elastic materials. With the emphasis firmly on the lithosphere, the book includes analyses of observations using the theoretical methods developed. Written for advanced undergraduates and beginning graduates of geophysics and planetary sciences, this is also of interest to civil engineers, seismologists, acoustical engineers, and others interested in wave propagation through inhomogeneous elastic media.